Pengaruh Pemberian Pakan Terhadap Pertumbuhan Dan Perkembangan Ikan Mas (Cypriynus carpio) - Hasibuan, Febry Rahmadhani; afrianti, Billah; Syahfitri, Dini Indah; Nayla; Amalia, Qoyum (Jurnal Biologi, 2023)
Goldfish (Cyprinus carpio) is a type of food fish which is a freshwater fishery commodity that has good prospects. Goldfish (Cyprinus carpio) are animals that live in temperate climates and live in freshwater ponds. The aim of this research is to determine the effect of providing these 3 feeds and to determine the development and growth of goldfish after being treated with these three feeds. The method used in this research is an experimental method by providing treatment with the three feeds. Based on the research results, it was found that the growth and development of goldfish can be influenced by several things, including: age, size, density and space for movement. Each type of fish food has a certain daily growth rate value which depends on water quality.